The usefulness of derivative disclosures for investment decision-making: Perceptions of Chinese institutional investors. Issue 3 (6th October 2014) - Huang, Zhen; Gao, Simon
Abstract : Purpose: – The purpose of this study is to examine the usefulness of derivative disclosures from the perspective of Chinese institutional investors in relation to their investment decision-making. Design/methodology/approach: – This study uses semi-structured interviews with 21 institutional investors based in China including 10 funds managers and 11 professional analysts. Findings: – This study finds that the information on the use of derivatives disclosed by listed companies in China is generally perceived to be useful to Chinese institutional investors (e.g. funds managers and professional analysts) in facilitating their investment decisions, although such information is generally thought to be less significant compared to other fundamental financial information such as assets, liabilities and profits/losses. It also finds that the current provisions of derivatives-related information by Chinese listed companies are largely unsatisfied primarily because of insufficient information and the lack of timely disclosures. Furthermore, it finds that the accounting and reporting policies currently imposed in China appear to be little understood by Chinese investors. Research limitations/implications: – This study has its own limitations due to the approach of interviews with a relatively small sample from only two investment firms in China. Practical implications: – The findings from the study provide a number of policy implications for derivatives regulators and accounting standards setters. Originality/value: – This study is the first study of its kind to investigate the perceptions of Chinese institutional investors on the usefulness of derivatives reporting and disclosures with the use of interview research method.